Analisis Tingkat Depresi, Ansietas dan Stres saat Menghadapi Penilaian Akhir Semester pada Siswi SMK Muhammadiyah - Susana Nurtanti; Sri Handayani (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2021)
Several stresors that occur in adolescents can cause various negative conditions, including anxiety, depression and psychotic disorders. Depressive conditions that last a long time and do not get the right treatment will cause mental problems in adolescents. Depression, anxiety and stress problems cause health problems for the next generation in Indonesia and the world. This study aims to determine the prevalence level of depression, anxiety and stress in female adolescents when final exams assessment at SMK Muhammadiyah Baturetno, Wonogiri Regency, Indonesia. The study used a descriptive quantitative design with a cross-sectional approach. The instrument applied in this study was the DASS42 questionnaire which had been applied in several previous studies. The population in the study were all teenage students at SMK Muhammadiyah Baturetno. The sampling technique used purposive sampling. The research sample was 289 female students at SMK Muhammadiyah Baturetno. Most of the respondents based on gender characteristics experienced mild stres as many as 112 (38.8%), based on the age characteristics experienced mild anxiety was at the age of 17 years a number of 52 (17.9%), based on class, the most experienced experienced anxiety. mild as many as 75 (25.9%) are class 1 respondents. The results of the study, the prevalence of depression was 35 (12.1%), anxiety was 115 (39.8%) and stress was 139 (48.1%).